Atomic order transition of TiNiPt nanoparticles supported on carbon nanotubes for the stable hydrogen evolution reaction. Issue 40 (27th September 2022) - Wei, Mengni; He, Mengdi; Wei, Xinyu; Gong, Shen; Luo, Liuxiong; Li, Teng; Tang, Shanguang; Zhu, Zhenghong
Abstract : TiNiPt nano-alloy particles overcome the kinetic energy barrier and undergo atomic level transformation, exhibiting excellent HER activity and stability. Abstract : Pt-based catalysts have achieved great success in the hydrogen evolution reaction (HER) due to their unique surface and electronic structures. In this paper, atomically ordered Ti50 Ni x Pt50− x /CNT and disordered Ti50 Ni x Pt50− x /CNT catalysts are prepared using a simple impregnation method. Compared with the disordered samples, the ordered ones exhibit excellent HER activity and stability in alkaline electrolytes. O-Ti50 Ni30 Pt20 /CNT can reach 10 mA cm −2 with only 21 mV overpotential, and the Tafel slope is 25.7 mV dec −1 . The stabilization time at 10 mA cm −2 is up to 80 h, which is about twice that of D-Ti50 Ni30 Pt20 /CNT. Both the samples show good HER performance in acidic electrolytes. According to the experimental and DFT calculation results, it is found that the ligand effects of Ni and Pt atoms can effectively accelerate the alkaline HER kinetics. The enhanced stability of the ordered TiNiPt/CNT sample originates from its fixed and ordered atomic arrangement, resulting in strong interactions between Pt and Ni–Ti bonds. This work provides a new structural design optimization approach for the study of acid–base HER electrocatalysts.